If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -34 = 2(x + -18) Reorder the terms: -34 + 3x = 2(x + -18) Reorder the terms: -34 + 3x = 2(-18 + x) -34 + 3x = (-18 * 2 + x * 2) -34 + 3x = (-36 + 2x) Solving -34 + 3x = -36 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -34 + 3x + -2x = -36 + 2x + -2x Combine like terms: 3x + -2x = 1x -34 + 1x = -36 + 2x + -2x Combine like terms: 2x + -2x = 0 -34 + 1x = -36 + 0 -34 + 1x = -36 Add '34' to each side of the equation. -34 + 34 + 1x = -36 + 34 Combine like terms: -34 + 34 = 0 0 + 1x = -36 + 34 1x = -36 + 34 Combine like terms: -36 + 34 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| 2.42 = p2 | | 3(3x-3)=21 | | (X+3)-2X=35+X | | 16(x+2)-4x=4(3x+2)-9 | | 8x+66=3x+31 | | x+46=5x+10 | | 89=1x+100 | | 24-9=5x | | 3/4(x-2)=-6 | | 10.44x=26.3 | | 5x(5+4)= | | CosX=-.08092 | | 7x+41=2x+11 | | 2x-4+3x=9 | | 63=5x+23 | | -3(3x+3)-2(1-14x)=3(6+6x) | | CosX=-.089092 | | 2x+17=-3-(-7x) | | 3/4(x-9)=-62 | | p-24=43 | | 5(z-3)=17.5 | | 180=24x-.4x^2 | | x+0.5y=0 | | -3/4(1/4) | | -3/4(1/5 | | (x+6)+(2-x)=16 | | X+(x+1)+(x+3)=41 | | -486=9(10x-5) | | 50x=80(x+-2) | | Tan(2x+36)=tan(5x+60) | | 14(x-2)+3x=42-(x-5) | | x+x=72 |